A brief history of happiness - White, Nicholas P., 1942-; Wiley InterScience (Online service) (Malden, MA ; Oxford : Blackwell Pub., 2006)
Do we really know what happiness is? Should happiness play such a dominant role in shaping and orienting our lives? And how can we deal with conflicts between the various things that make us happy? In this'Brief History of Happiness', philosopher Nicholas White reviews 2,500 years of attempts to answer such questions. White considers the ways in which major thinkers from antiquity to the present day have treated happiness: from Plato's notion of the harmony of the soul and Aristotle's account of well-being or flourishing as the aim of an ethical life, to Aquinas' idea of the vision of the divine essence, Bentham's hedonistic calculus, and the modern-day decision-theoretic notion of preference. We also encounter skepticism about the very idea of a complete and consistent concept of happiness in the writings of Nietzsche and Freud. Throughout, White relates questions about happiness to central concerns in ethics and practical philosophy.
Introducing the subject -- Conflicts, perspectives, and the identification of happiness -- Pleasure, hedonism, and the measurement of happiness -- Happiness as structure and harmony -- Morality, happiness, and conflict -- Happiness, fact, and value -- Doing without the concept.
Includes bibliographical references (pages 181-186) and index.
Print version record.
Keywords: Happiness -- History; Bonheur -- Histoire; PHILOSOPHY -- Social; PHILOSOPHY -- Ethics & Moral Philosophy; Happiness; Electronic books; History